Analisis Proses Rekrutmen dan Seleksi Karyawan pada Sektor Jasa Konstruksi di PT Asuka Engineering Indonesia - Ananda Revi Faizah; Heru Baskoro (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines PT Asuka Engineering Indonesia, a company operating in the construction services sector, with a primary focus on the challenges faced by the company in the recruitment process to ensure an efficient and high-quality workforce. Recruitment is a crucial aspect in maintaining the continuity and quality of construction projects. Therefore, the purpose of this research is to analyze the implementation of the Standard Operating Procedures (SOP) in the recruitment process and identify the obstacles faced by the company in meeting its human resource needs. The research approach used in this study is descriptive qualitative, with data collection through structured interviews conducted with relevant parties within the company. The findings of this study revealed that although PT Asuka Engineering Indonesia has well-structured recruitment SOPs, the implementation still faces various challenges. Some of the identified obstacles include a lack of proper planning regarding human resource needs, ineffective coordination between divisions, and budget constraints to meet the urgent and unexpected human resource demands. These issues have caused the recruitment process to not always run smoothly, leading to a mismatch between the required workforce and the available qualified human resources. Based on these findings, it is recommended that the company improve its human resource planning process, focusing on more accurate predictions of labor needs, and strengthen coordination between divisions to ensure a smoother recruitment process. Enhancing communication between departments is also essential to ensure that every division can work synergistically and complete the recruitment process on schedule and as needed. The implications of these findings suggest that improvements in planning, budgeting, and communication are necessary to ensure that the recruitment process is more effective, efficient, and timely.